P289 Finding the missing millions – the impact of a locally enhanced service for COPD on current and projected rates of diagnosis. (19th November 2012) - Falzon, C; Soljak, M; Elkin, SL; Blake, ID; Hopkinson, NS
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is a common and important condition but there is a considerable gap between the modelled and diagnosed prevalence of the disease.(1) In 2008 a locally enhanced service (LES) for COPD was introduced in our Primary Care Trust (PCT) which included a small financial incentive for GP's to perform spirometry but a larger one where COPD patients were identified and received additional quality items of care including; spirometry and pulse oximetry; smoking cessation; recording of BMI and MRC dyspnoea score; review of inhaler technique; medication review; provision of a COPD rescue pack if appropriate; issuing a self-management plan; influenza and pneumococcal vaccination. In the first year this encouraged GP's to focus case-finding efforts on those most likely to have COPD and led to a significant step up in the diagnosed prevalence.(2) Methods: To evaluate longer term effects we used annual QOF reporting-year data on prevalence of COPD at PCT level from 2005 through to March 2011 obtained from the QMAS database via the NHS Information Centre. COPD prevalence data for the 4 years from the introduction of the LES (2008) were used to compare trends in COPD diagnosis between the PCT where it had been introduced, a neighbouring PCT, the London SHA and England. True COPD prevalence was estimated using data from the Health Survey for England. Diagnosed prevalence trends were extrapolated to estimate the year this level would be reached. Results: The rate of increase in COPD diagnosis with the LES remained significantly increased compared to that for London as a whole (Figure 1 ). Extrapolating 2008–2011 trends in prevalence, the PCT where the LES was in place would be expected to reach the modelled prevalence of COPD in 2030 whereas London as a whole would not reach the true prevalence until 2080. Conclusion: Current strategies for COPD case finding are inadequate given the scale of the problem. With appropriate incentives it is possible to achieve a sustained improvement in case-finding and such policies need to be implemented systematically. Nacul L, Soljak M, Samarasundera E, Hopkinson NS, Lacerda E, Indulkar T, et al. COPD in England: a comparison of expected, model-based prevalence and observed prevalence from general practise data. J Public Health. 2011; 33(1): 108–16. Falzon C, Elkin SL, Kelly JL, Lynch F, Blake ID, Hopkinson NS. Can financial incentives for improvements in healthcare quality enhance identification of COPD in primary care? Thorax. 2011; 66(7):630.